Dynamic Changes of Behavioral Despair, HPA Axis Activity, and Hippocampal Neurogenesis in Male Rats Induced by Social Defeat Stress - Hiroyoshi Harada; Masayoshi Mori; Yusuke Murata; Shunsuke Kawanabe; Kazuki Terada; Taichi Matsumoto; Kenji Ohe; Munechika Enjoji (Journal of Integrative Neuroscience, 2023)
Background: Psychosocial stress factors, such as threat and defeat, are major risk factors for the development of depression. The precise mechanisms underlying stress-induced depression are not clearly understood because the stress response in the brain varies in a stress-frequency-dependent manner. In the current research milieu on the pathogenesis of depression, the focus is on depression-like behavioral phenotype, hypothalamic-pituitary-adrenal (HPA) axis, and hippocampal neurogenesis. However, most studies have evaluated the symptomatic features of depression at certain time points after exposure to psychosocial stress. Here, we examined the frequency-dependent effects of psychosocial stress on depression-related features in rats. Methods: In the present study, different frequencies (one, two, three, or four times) of psychosocial stress were applied to 19 male Sprague-Dawley rats using a resident/intruder paradigm. Subsequently, the rats were subjected to a stress reactivity test to evaluate HPA axis activity, following which assessments of immobility behavior in the forced swimming test (FST) and adult neurogenesis were conducted. Results: One-time stressed rats showed a decrease in immobility behavior in the FST and the amount of doublecortin (DCX)-positive cells. Two-time stress caused hypoactivity of the HPA axis. In contrast, immobility behavior and HPA axis activity were increased after four-time stress exposure, but the number of DCX-positive cells was decreased. Conclusions: Our findings suggest that psychosocial stress produces a biphasic effect on the symptoms of depression in a stress-frequency-dependent manner, which could provide insights to facilitate further pathogenesis research on depression.